Effects of dietary lysine level on growing pig performance - D F Li; M E Johnston; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1989)
A growth trial utilizing 120 pigs (avg initial wt 43.4 lb) was conducted to investigate the lysine requirement for pigs weighing 45 to 75 lb. Pigs were fed a corn-soybean meal diet containing .65, .75, .85, .95, or 1.05% lysine. Average daily gain (ADG) and feed/gain (F/G) were determined weekly, and plasma urea concentration was determined at the end of the first and last week of the experiment. At d 14, ADG was increased and F/G improved with increasing lysine level. Gain was best for pigs fed the .95% lysine diet at d 14 and for those fed .85% lysine at d 28. Feed efficiency was optimized for pigs fed diets containing .95% lysine at d 14 and 28 of the experiment. Plasma urea concentration on d 7 indicated that .85% lysine was optimum. However, by d 28, plasma urea concentration indicated that .75% lysine was adequate. Our results indicate that growth performance of pigs weighing 45 to 75 lb was optimized by a diet containing at least .85% lysine.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Lysine; Performance; Growing pig